Knowledge and awareness regarding thyroid disorder among paramedical students - Abirami, R. Sakthi; Subiksha, E.; Mubasheer, K. F. Mohammed; Swetha, M.; Padmaja, S. (International Journal Of Community Medicine And Public Health, 2024)
Background: Thyroid disease ranks as the second most common endocrine disorder worldwide, following diabetes. In India, the prevalence mirrors global trends, with approximately 42 million individuals affected, accounting for one in ten adults. Methods: A cross-sectional study was conducted with 1064 paramedical students aged 18-25 years. The study received approval from the institutional ethics committee, and informed consent was obtained from all participants. Data on knowledge and awareness were collected using a questionnaire. Statistical analysis, including frequency, mean, standard deviation, percentage was performed using SPSS version 2.0. Results: The study found that 31.86% of students had a low level of knowledge about thyroid disorders, while 24.90% demonstrated a high level of knowledge on thyroid symptoms. Additionally, 8.17% of students showed good awareness of thyroid disorders, whereas 42.01% had low awareness levels. Third-year students aged 20-22 exhibited higher awareness (12.40%) of lifestyle factors and preventive measures affecting thyroid health. Conclusions: There were significant gaps in knowledge and awareness of thyroid disorders among paramedical students. Enhancing education and outreach efforts could help bridge these gaps, empowering individuals to recognize symptoms, seek timely diagnoses, and access appropriate treatment.